Experimental research on salt contamination procedures and methods for assessment of the salt distribution. (6th September 2021) - Nunes, Cristiana; Maria Aguilar Sanchez, Asel; Godts, Sebastiaan; Gulotta, Davide; Ioannou, Ioannis; Lubelli, Barbara; Menendez, Beatriz; Shahidzadeh, Noushine; Slížková, Zuzana; Theodoridou, Magdalini
Highlights: A procedure for accumulating salts at the surface of porous materials is proposed. Most of the salt is concentrated in the first millimetres of the subsurface. The measurement of the salt distribution is crucial in salt crystallisation tests. Abstract: The RILEM TC ASC-271 is developing a new laboratory test to assess the durability of porous building materials to salt crystallisation. The test encompasses two phases: salt accumulation and damage propagation. This paper focuses on designing a procedure for the accumulation phase; this is considered successful when salts crystallise at the material's evaporative surface (common situation observed on site) without the occurrence of damage. Two procedures were developed and tested on two limestones with different porosity: (1) capillary absorption of a salt solution followed by drying, and (2) continuous capillary absorption. Sodium chloride or sodium sulphate solutions were used. Several methods for assessing the salt distribution were employed: ultrasonic pulse velocity, drilling/scratching resistance, hygroscopic moisture content, ion chromatography, scanning electron microscopy, and micro X-ray fluorescence. The results enabled the selection of the most effective protocol for the salt accumulation phase.